Modeling the current voltage characteristic of graphene nanoribbons field effect transistor at different subband [electronic resources] - Wong, King Kiat 1988; Razali Ismail, supervisor (2012)
Project Paper (Sarjana Muda) - Universiti Teknologi Malaysia, 2012